1997
DOI: 10.1111/j.1528-1157.1997.tb01199.x
|View full text |Cite
|
Sign up to set email alerts
|

What is the Relationship Between Arachnoid Cysts and Seizure Foci?

Abstract: Summary:Purpose: Arachnoid cysts are sometimes encountered in MRIs performed for a variety of reasons. In patients with epilepsy, particularly those with refractory epilepsy, arachnoid cysts are often assumed to be related to their seizure focus. We conducted a study to investigate this putative relationship.Methods: A retrospective study on the incidence of arachnoid cysts was performed in patients seen in our Epilepsy Clinic who had CT or MRI scans, interictal EEGs or ictal EEGS. Locations of seizure foci in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 10 publications
6
45
0
2
Order By: Relevance
“…In our series, the cognitive impairment persisted despite surgery. The causative relationship between ACs and epileptic seizures is controversial [22]. Similar to our results, some studies find a complete resolution of seizures in some patients, while other patients experience either a reduced or an unchanged frequency of seizures [23].…”
Section: Discussionsupporting
confidence: 78%
“…In our series, the cognitive impairment persisted despite surgery. The causative relationship between ACs and epileptic seizures is controversial [22]. Similar to our results, some studies find a complete resolution of seizures in some patients, while other patients experience either a reduced or an unchanged frequency of seizures [23].…”
Section: Discussionsupporting
confidence: 78%
“…In clinical practice, however, more often brain cysts without signs of compression are observed in epileptic patients, raising the question whether the cyst content may be relevant for epileptogenesis. In a retrospective analysis of 867 patients of whom 17 had arachnoid cysts, only in 4 patients the seizure focus was adjacent to the cyst, suggesting that arachnoid cysts are often incidental findings in epileptic patients (Arroyo and Santamaria, 1997). A similar conclusion was recently reached by Yalcin et al (2002), who reported that seizure type and EEG abnormalities corresponded to arachnoid cyst location in only one out of eight patients.…”
Section: Introductionsupporting
confidence: 56%
“…Incidence is 0.5% in autopsy series [7]. However, there are also different percentages reported in the literature: 0.23% in head trauma, 1.96% in epilepsia, and 2.6% in headache [8][9][10]. Generally arachnoid cysts remain asymptomatic but may cause headache, nausea, vomiting, lethargy, seizures, and focal symptoms of space-occupying lesion.…”
Section: Discussionmentioning
confidence: 96%